Secondary metabolites of Hericium erinaceus against neurodegenerative diseases - Hellmann, Bernhard; Justus Liebig University Giessen (My University, 2023)
Alzheimer’s disease (AD) is increasing in prevalence, and the WHO estimates that more than 150 million people will be affected by 2050. The most significant factors influencing AD appear to be a combination of age-related changes in the brain, genetic predispositions, environmental influences, and lifestyle factors. On the molecular level, late-stage AD is characterized by mitochondrial dysfunction, increased reactive oxygen species (ROS) levels, amyloid-β (Aβ) protein aggregates, increased tau levels, and neurodegeneration. Currently, there are no existing treatments that can cure the disease; therefore, prevention and mitigation of symptoms are crucial. Several compounds isolated from plants and mushrooms have shown beneficial effects in treating Alzheimer's disease (AD) by targeting different pathological mechanisms. Among these, erinacines, identified in the edible mushroom Hericium erinaceus, are particularly promising compounds that modulate disease progression. Extracts from this mushroom, rich in erinacines, have demonstrated potential to enhance mitochondrial function and promote neuronal health, suggesting a preventive approach against AD. Notably, studies have shown that erinacines stimulate Neuronal Growth Factor (NGF) production and neuritogenesis, indicating their key role in preventing the progression of AD. In particular, erinacine C has the strongest effects on NGF stimulation; however, it is scarce because it is produced only in the mycelium of the mushroom. In the present work, erinacine C was produced through submerged cultivation of Hericium erinaceus, followed by isolation and characterization using HPLC-DAD, NMR, and HR- MS. Erinacine C was tested in SH-SY5Y, MOCK, and APP696 cells. Furthermore, an ethanolic mycelium extract of Hericium erinaceus was tested in the SH-SY5Y cell lines as well as in Caenorhabditis elegans CL2122 and GMC101 strains. To test the hypothesis on the mitochondrial effects of erinacine C, experiments on cell viability, mitochondrial membrane potential, ATP levels, mitochondrial mRNA expression (SIRT1, CREB1, NRF1, TFAM, and ATP5D), respirometry, neurotoxicity, neuritogenesis, and Aβ levels were conducted. Results showed that erinacine C had positive effects in SH- SY5Y cells, including increased ATP levels, decreased oxidative stress, and elevatedexpression of NRF1. Additionally, treatment activated genes related to axon guidance and actin binding, linking the genomic results with the in vitro data of positive neuronal outgrowth. Through RNA-seq analysis, the research scope expanded beyond just the mitochondria. On the other hand, the Hericium erinaceus ethanolic extract showed increasing effects at low concentrations on the lifespan in GMC101 but not in CL2122. However, ATP levels in GMC101 were elevated after treatment. The extract was tested in SH-SY5Y cells to evaluate viability, ATP levels, and the expression of mitochondrial genes. Due to the unknown matrix components, no clear conclusion related to erinacine C could be drawn. Nevertheless, these findings underscore the potential of Hericium erinaceus to be used as part of a preventive strategy against AD, leveraging its mitochondrial and neuroprotective properties. Altogether, the results presented here pave the way for more comprehensive studies to elucidate further the mechanisms through which Hericium erinaceus and its compounds, like erinacine C, confer neuroprotective benefits. The RNA-seq results suggest that erinacine C exhibits hormone-like effects on human neuronal cells. Future research should aim to better understand the mechanisms of action of these compounds and their potential in clinical settings.
Keywords: Alzheimer's Disease; Hericium erinaceus; Erinacine C; SH-SY5Y; Caenorhabditis elegans; ddc:570; ddc:500; ddc:610